A comprehensive approach: Diffusion of environment-friendly energy technologies in residential photovoltaic markets - Adnan, N. (Elsevier Ltd, 2021)
The rapid upsurge in distributed solar adoption in Malaysia provides an opportunity for adopters to lower electricity bills and gain additional community benefits, including grid stability and lower grid emissions. The main factors for rising electricity generation from renewable fuels are gaining independence from fossil fuels and combating climate change. Solar photovoltaic (PV) is believed to have the most significant potential between renewable technologies. The National energy strategies have stated that a renewable energy system, such as a photovoltaic (PV) system, plays a vital role in the minimization of energy consumption. Therefore, the successful installation has given rise to a progressive response cycle whereby amplified customer acceptance resulted in reduced demand from Utility providers. However, the number of individuals adopting solar photovoltaic technologies is still comparatively small. Elsewhere, innovation and monetary influences and ecological incentives seem to be significant for associating renewables with energy reserves. However, this paper has highlighted numerous factors that were founded on the modified norm simulation model based on the Theory of planned behavior (TPB) and value-belief-norm theory (VBN). The researcher examined how eco-friendly enthusiasm and other socio-psychological, socio-technical, and socio-economic aspects influence the PV adoption behavior among households consumers. Several norms reinforce the customer adoption rates of the PV system. Also, researchers have discussed the current trends and benefits towards the adoption of PV systems, whereas past research in PV systems has only been discussed in the domain of monetary benefit. Lastly, some future research directions are suggested for further advancement towards the reduction of energy consumption, which will lead to new insights for policymaking concerns and from the consumer aspect. Â© 2021 Elsevier Ltd